STRATEGIC MANAGEMENT IN SUSTAINABLE EDUCATION THROUGH INTEGRATION OF ENVIRONMENTAL EDUCATION IN THE NATIONAL CURRICULUM - Nurul Hidayah; Murtando; Muhammad (Evaluasi : Jurnal Manajemen Pendidikan Islam, 2025)
Abstract . Environmental education in the national curriculum plays an important role in shaping the awareness of the younger generation towards global environmental issues. This study aims to describe a comprehensive strategic management to integrate environmental education into the national curriculum, considering the local and global contexts of sustainable education towards implementation, obstacles, challenges and supporting and inhibiting factors. The research method with a qualitative descriptive approach, this study focuses on Madrasah Ibtidaiyah Masyarikul Anwar IV Sukabumi, which has successfully implemented environmental education through the Adiwiyata program. Data were collected through observation, documentation, and content analysis of school activities. Data were analyzed using content analysis where researchers analyzed the contents of the documents that had been collected. The stages in data analysis include data reduction; data presentation; and drawing conclusions. The results of the study indicate that the success of the implementation of environmental education is greatly influenced by school commitment, community involvement, and support from teachers. However, there are obstacles in the form of limited resources, lack of teacher training, and dynamic curriculum changes. In conclusion, the strategic management framework can support the integration of sustainable environmental education, with important notes on the existence of policy support, adequate resources, and collaboration between stakeholders so that environmental education can develop optimally and consistently in the national education system.